Laboratory Study Of A Suitable Demulsifier For Implementation In Ramba Field - Rahmat Ernowo; Nur Suhascaryo (Journal of Petroleum and Geothermal Technology, 2026)
This study was conducted to identify the optimal demulsifier composition capable of breaking water-in-oil (W/O) emulsion found in the production fluid at the Ramba Gathering Station (with a water-to-oil ratio of 60:40). Initial effectiveness was evaluated on seven single active agents across three types (water drop, interface, and clear water) to select the best agent from each category. The selected active agents were then blended to produce eight new demulsifier compositions (RE-1 to RE-4), by varying the component percentages, including a variation with the addition of 5% acid to assess its synergistic effect on emulsion separation performance. The tests were performed using the standard bottle test method with a demulsifier injection dosage of 200 ppm and heated at 40°. The main focus of the test was to compare the degree of emulsion destabilization, the quality of the oil-water interface formed, and the clarity of the separated water phase. The performance of the demulsifier compositions (RE-1 to RE-4) was directly compared against the same versions formulated with 5% acid, as well as against a control sample (Blank) without chemical treatment. Observation results consistently showed that the addition of 5% acid significantly enhanced the emulsion breaking performance across all composition samples. The acid-enhanced demulsifiers (RE-1 to RE-4) produced an oil-water interface that was far more stable, distinct, and easier to observe, and resulted in a clearer water phase compared to formulations without the 5% acid addition. The improved water clarity indicates a much more effective coalescence and settling process. Overall, this study concludes that the addition of 5% acid proved to be a crucial factor in improving demulsifier effectiveness and optimizing production fluid processing at the Ramba field.